BAKTI “TERARAH”: UPAYA PENINGKATAN KESEHATAN DENGAN PEMERIKSAAN TEKANAN DARAH DAN GULA DARAH “TERARAH” BAGI WARGA DESA PULO PANJANG – KABUPATEN SERANG - Rahmatullah, Asep; Wijaya Kusuma, Jaka; Fauzah, Siti; Citra Dae Geri, La Fitriyani; Amsilah, Amsilah; Rosalia, Rosalia (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
The critical health of rural communities is due to the low understanding and awareness of the public about health checks on non-communicable diseases such as hypertension (high blood pressure) and Diabetes Mellitus (DM or High Blood Sugar). Based on preliminary studies and observations in Pulo Panjang Village, it shows that the high intensity of capture fisheries activities (livelihoods) in the community, has an indirect impact on the low level of public awareness of health checks, plus the limited time of medical personnel on duty at the Pulo Panjang Village Health Post (Poskesdes) which only ranges from 10.00 – 14.00 WIB (Monday – Friday). This community service aims to increase the level of public awareness of the importance of health checks (Blood Pressure and Blood Sugar) early so that the results of these examinations become a reference for the community to be able to implement a healthy lifestyle as an effort to prevent worse health impacts due to high blood pressure and blood sugar. The method of implementing community service "BAKTI Terdir" is carried out using 2 methods, namely counseling and early examination (Screening). The results of the KKM-PkM "BAKTI TERTITI" activity received very high appreciation from the community, shown by the enthusiasm of the participants who participated reached 120 participants and it is hoped that there will be additional programs for participants who are included in the category of further handling by providing obast for free.